2011
DOI: 10.1007/s12257-011-0213-5
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of the halophyte Limonium tetragonum and its major active components

Abstract: In this study, the antioxidant potentials of crude extracts and solvent-partitioned fractions of Limonium tetragonum were assessed by measuring their ability to scavenge intracellular reactive oxygen species (ROS) generated in HT-1080 cells. Following activity-oriented separation, four flavonol glycosides were isolated as active principles and their chemical structures were determined by 2 D NMR and by comparison with reported spectral data. The isolated compounds (1-4) were evaluated for their antioxidant cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…9) It has been widely used in treating uterine hemorrhage, oligomenorrhea, dysgalactia, and tinnitus. 10) The edible buds and shoots of L. tetragonum contains several active compounds like myricetin glycosides and quercetin glycosides. 11) Crude extracts and fractions from halophyte L. tetragonum exhibited biological properties such as anticancer and antioxidant activities.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…9) It has been widely used in treating uterine hemorrhage, oligomenorrhea, dysgalactia, and tinnitus. 10) The edible buds and shoots of L. tetragonum contains several active compounds like myricetin glycosides and quercetin glycosides. 11) Crude extracts and fractions from halophyte L. tetragonum exhibited biological properties such as anticancer and antioxidant activities.…”
mentioning
confidence: 99%
“…11) Crude extracts and fractions from halophyte L. tetragonum exhibited biological properties such as anticancer and antioxidant activities. 11,12) Although salt-tolerant plants including L. tetragonum have been recognized as one of the most important ecosystems in a tidal zone, biological and phytochemical studies on halophyte vegetation have been little reported yet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18][19][20] Of these, most compounds were reported that were polyphenolic compounds. Polyphenols have been reported to have various biological activities that result in antioxidant, anti-hyperlipidemic, anti-cancer, and anti-inflammatory effects.…”
Section: 10mentioning
confidence: 99%
“…[16][17][18] Our previous researches mainly focused on the liver protection of L. tetragonum by suppression of hepatic satellite cells (HSC-T6) proliferation, 19) liver injury induced by acute alcohol, 20) and diethylnitrosamine-induced liver fibrosis. 21) However, current studies do not contain any reports on the beneficial effects of certain extract from L. tetragonum in prevention and/or treatment of obesity.…”
mentioning
confidence: 99%